2019
DOI: 10.1002/spe.2760
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised software repositories mining and its application to code search

Abstract: Software repositories are crucial resources for many software tasks, including code retrieval and annotation. Programming forums provide questions and answers (Q&A) from software developers, containing abundant code-description posts for exchanging knowledge about programming issues. However, most posts provide personal opinions of users that are often not adequately confirmed or outdated. Mining software repositories in such open and unrestricted forums is challenging. Since the posts can be arbitrary and noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…However, the major challenge is the semantic gap between query and code. Code is not like a search query and code is written in a highly structured programming language with different syntactic rules and semantic representation [42,83,150]. To address this issue, researchers have proposed many query processing techniques to align this semantic gap, such as replacing query words with appropriate synonyms that occur in the codebase [134]; and expanding query words with code changes (e.g., pull requests and commits) in the development history [44-47, 52, 52, 150].…”
Section: Classification Of Code Search Tasksmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the major challenge is the semantic gap between query and code. Code is not like a search query and code is written in a highly structured programming language with different syntactic rules and semantic representation [42,83,150]. To address this issue, researchers have proposed many query processing techniques to align this semantic gap, such as replacing query words with appropriate synonyms that occur in the codebase [134]; and expanding query words with code changes (e.g., pull requests and commits) in the development history [44-47, 52, 52, 150].…”
Section: Classification Of Code Search Tasksmentioning
confidence: 99%
“…It has been observed that APIs are an important factor to complement the missing semantics in queries [8]. Researchers have thus expanded query words with relevant APIs or class names from official API documents [83], codebases [140], or Stack Overflow posts [11,42,95,118,143].…”
Section: Classification Of Code Search Tasksmentioning
confidence: 99%
See 3 more Smart Citations